The Construction of the Main Child Character’s Identities in Matilda (1996) - Chitra Yunia Mahmudah (Universitas Pendidikan Indonesia (UPI), 2018)
This study entitled The Construction of the Main Child Character’s Identities in Matilda (1996) aims to reveal the construction of Matilda’s identities and to derive meanings behind the construction. This study uses textual analysis and employs theories of identities from Burke and Stets (2009) as well as Boggs and Petrie’s (2008) concept of characterizations, and film style from Bordwell and Thompson (2008). The findings show that Matilda has multiple identities which are constructed based on three bases of identities. Her multiple identities are established through her characterization and supported by cinematic aspects such as shot, color, lighting, and sounds. From the analysis, her character is seen as a non-mainstream construction. She is presented to be more mature than and not necessarily as innocent as other child characters in general. Keywords: children’s films, film style, identity